2021
DOI: 10.1007/s00420-021-01775-y
|View full text |Cite
|
Sign up to set email alerts
|

Front lines of the COVID-19 pandemic: what is the effectiveness of using personal protective equipment in health service environments?—a systematic review

Abstract: Purpose This systematic review aimed to evaluate the effectiveness of the use of personal protective equipment (PPE) in closed environments, similar to waiting or exam rooms of healthcare facilities, in the face of exposure to a bioaerosol. Methods Combinations of words were selected for six electronic databases and for the gray literature. To consider the eligibility of the studies to be included/excluded, the acronym “PECOS” was used: humans and/or experimental models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…Given this decrease, and without the action of the vaccines, the most plausible explanation could be the improvement of the non-pharmaceutical preventive measures implemented at PSMar. These include the availability of adequate PPE, the correct use of which reduces significantly the transmission of infection [ 19 , 20 ] and universal screening, i.e., testing both symptomatic and asymptomatic HCWs, which is vital for effective cases detection and, thus, for limiting transmission [ 20 , 21 ]. According to hospital documentation and the information from key informants (occupational risk prevention technicians and head of the logistics department of PSMar, personal communication, June 2021), the lack of equipment during the first weeks of the pandemic was gradually overcome from mid-April (week 17) onwards, stabilising the purchase and distribution of adequate PPE (mainly FPP2 and sanitary masks, eye protection and gowns) available to all healthcare workers by the end of June.…”
Section: Discussionmentioning
confidence: 99%
“…Given this decrease, and without the action of the vaccines, the most plausible explanation could be the improvement of the non-pharmaceutical preventive measures implemented at PSMar. These include the availability of adequate PPE, the correct use of which reduces significantly the transmission of infection [ 19 , 20 ] and universal screening, i.e., testing both symptomatic and asymptomatic HCWs, which is vital for effective cases detection and, thus, for limiting transmission [ 20 , 21 ]. According to hospital documentation and the information from key informants (occupational risk prevention technicians and head of the logistics department of PSMar, personal communication, June 2021), the lack of equipment during the first weeks of the pandemic was gradually overcome from mid-April (week 17) onwards, stabilising the purchase and distribution of adequate PPE (mainly FPP2 and sanitary masks, eye protection and gowns) available to all healthcare workers by the end of June.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al stated that N95 respirators are superior to surgical masks [ 16 ]. The fourth study found that better protection can be achieved when the surgical masks are used by the aerosol source (infected person) rather than when the recipient wears the N95 respirator [ 17 ]. The last study concluded that surgical masks or N95 respirators alone do not provide complete protection [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…A systematic review concluded that there is no clear evidence that surgical masks are less effective than N95 respirators in protecting HCWs from laboratory-confirmed respiratory viral infections during routine care and non-aerosol-generating procedures [ 15 ]. Another systematic review stated that the use of surgical masks by the source of infectious aerosol generators offers higher protection than the use of N95 respirators by the recipient [ 17 ]. Accordingly, the risk of exposure can be decreased by having everyone in the area use masks with lower filtration efficiency instead of employing respirators with high filtration efficacy only for some people in the area [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“… 7 Additionally, current influenza vaccine technologies cannot be preemptively deployed in anticipation of pandemic influenza; instead, they can be implemented only in response to a pandemic that is already underway. Nonpharmaceutical interventions (NPIs), such as mask wearing, hand hygiene, indoor ventilation, quarantine of symptomatic individuals, and social distancing for asymptomatic persons are variably effective at preventing the spread of influenza and other respiratory viruses, 8 , 9 , 10 including pandemic SARS‐CoV‐2, 11 , 12 , 13 , 14 although the simultaneous implementation of multiple NPIs may be more effective than any one NPI alone. 9 , 12 Additional pathogen‐nonspecific interventions that are effective at hindering or preventing person‐to‐person disease transmission and that can be implemented in concert with other NPIs may help to mitigate the impact of future zoonoses like COVID‐19 or pandemic influenza.…”
Section: Introductionmentioning
confidence: 99%